1980
DOI: 10.1126/science.6254158
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Epidermal Growth Factor Receptors on 3T3 Cells by Platelet-Derived Growth Factor

Abstract: Platelet-derived growth factor does not compete with epidermal growth factor (EGF) for binding to EGF receptors on the murine 3T3 cell surface, but it modulates EGF receptors in two ways: (i) it induces a transient down regulation of EGF receptors and (ii) it inhibits EGF-induced down regulation of EGF receptors. These data suggest a common cellular internalization mechanism for the receptors for both hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1
3

Year Published

1982
1982
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(72 citation statements)
references
References 20 publications
5
63
1
3
Order By: Relevance
“…PDGF also was found to inhibit the binding of 125I-EGF to monolayers of these cells (Fig. 1) in a manner similar to that reported for other fibroblasts (4)(5)(6)(7)(8)(9). Addition of the tumor promoter PMA to the fibroblasts similarly caused a decrease in the binding of 125I-EGF (Fig.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…PDGF also was found to inhibit the binding of 125I-EGF to monolayers of these cells (Fig. 1) in a manner similar to that reported for other fibroblasts (4)(5)(6)(7)(8)(9). Addition of the tumor promoter PMA to the fibroblasts similarly caused a decrease in the binding of 125I-EGF (Fig.…”
supporting
confidence: 78%
“…Interestingly, this effect is also characteristic of tumor-promoting phorbol diesters such as 4p-phorbol 12/3-myristate 13a-acetate (PMA), which stimulate the growth of quiescent fibroblasts synergistically with EGF and insulin (2,3). An-other striking similarity between the actions of PDGF and phorbol diesters is a rapid inhibition of 125I-labeled EGF (125I-EGF) binding to the receptors ofcultured cells (4)(5)(6)(7)(8)(9)(10)(11)(12). In view of the similarity of these actions of PDGF and PMA on the EGF receptor, we considered the possibility that these two agents may have a similar mechanism of action.…”
mentioning
confidence: 99%
“…The EGF receptor is negatively modulated by a mechanism mediated by PKC and activated by PDGF and bombesin (3,5,9,36,37). We have shown that an analogous feedback mechanism appears to be triggered also by EGF itself, through the activation of PKC.…”
Section: Kinetics Of Tyrosine Phosphorylation Of Egf Receptor P-tyrmentioning
confidence: 86%
“…Platelet-derived growth factor can also act by modulating other growth factors. For example, in the 3T3 cell system, PDGF modulates EGF receptor by inducing a transient loss of EGF binding activity, independently of any change in EGF receptor affinity [258]. In serumcontaining medium, FGF was shown to decrease the differentiation of TA1 cells [166,167].…”
Section: Other Growth Factors and Cytokinesmentioning
confidence: 99%